Ultra-large scale AFM of lipid droplet arrays: investigating the ink transfer volume in dip pen nanolithography. (9th April 2015) - Förste, Alexander; Pfirrmann, Marco; Sachs, Johannes; Gröger, Roland; Walheim, Stefan; Brinkmann, Falko; Hirtz, Michael; Fuchs, Harald; Schimmel, Thomas
Abstract: There are only few quantitative studies commenting on the writing process in dip-pen nanolithography with lipids. Lipids are important carrier ink molecules for the delivery of bio-functional patters in bio-nanotechnology. In order to better understand and control the writing process, more information on the transfer of lipid material from the tip to the substrate is needed. The dependence of the transferred ink volume on the dwell time of the tip on the substrate was investigated by topography measurements with an atomic force microscope (AFM) that is characterized by an ultra-large scan range of 800 × 800 μ m 2 . For this purpose arrays of dots of the phospholipid1, 2-dioleoyl-sn-glycero-3-phosphocholine were written onto planar glass substrates and the resulting pattern was imaged by large scan area AFM. Two writing regimes were identified, characterized of either a steady decline or a constant ink volume transfer per dot feature. For the steady state ink transfer, a linear relationship between the dwell time and the dot volume was determined, which is characterized by a flow rate of about 16 femtoliters per second. A dependence of the ink transport from the length of pauses before and in between writing the structures was observed and should be taken into account during pattern design when aiming at best writing homogeneity. The ultra-large scan range of the utilized AFM allowed for a simultaneous study of the entire preparation area of almost 1 mm 2, yielding good statistic results.